Assessment of oppositional defiant disorder and oppositional behavior in children and adolescents with Down syndrome - Fucà, Elisa; Cirillo, Flavia; Celestini, Laura; Alfieri, Paolo; Valentini, Diletta; Costanzo, Floriana; Vicari, Stefano (Frontiers in Psychiatry, 2023)
Children and adolescents with intellectual disability exhibit higher rates of oppositional defiant disorder (ODD) than typically developing peers. However, studies focusing on the investigation of ODD prevalence in youth with Down syndrome (DS) are still limited. The current study aimed to investigate the prevalence of ODD clinical and subclinical symptoms in a group of 101 youth with DS (63 boys, 38 girls) ranging in age from 6 to 18 years. Moreover, the prevalence of ODD symptoms, as detected by means of three parent-report questionnaires, was compared with that detected by a semi-structured psychopathological interview, namely the Schedule for Affective Disorders and Schizophrenia for School Aged Children Present and Lifetime Version DSM-5. We found that 17% of participants met diagnostic criteria for ODD on the K-SADS, whereas 24% exhibited subclinical symptoms. Results also suggest good specificity of Swanson, Nolan, and Pelham–IV Rating Scale, Conners’ Parent Rating Scales Long Version (CPRS) and Child Behavior Checklist in detecting ODD symptoms. The investigation of the agreement in the prevalence rates of clinical and subclinical symptoms of ODD between K-SADS and the parent-report questionnaires indicated CPRS as the parent-report questionnaire with the best agreement with K-SADS. This study provides support for the use of parent-report questionnaires to assess ODD symptoms in children and adolescents with DS by evaluating their levels of agreement with a semi-structured psychopathological interview. In particular, our results suggest that CPRS could be considered a suitable screening tool for ODD clinical and subclinical symptoms in youth with DS.